LHCP four patches stack triangular truncated antenna using corporate feed microstrip-line for CP-SAR sensor - Muhammad Fauzan Edy Purnomo; Vita Kusumasari; Rudy Yuwono; Rahmadwati Rahmadwati; Rakhmad Romadhoni; Azizurrahman Rafli; Yuyu Wahyu; Akio Kitagawa (Institute of Advanced Engineering and Science, 2021)
In this paper, we acquire the configuration of the left-hand circular polarization (LHCP) array four patches stack triangular truncated microstrip antenna. This construction use the basic corporate feed microstrip-line with modified lossless T-junction power divider on radiating patch for circularly polarized-synthetic aperture radar (CP-SAR) sensor embedded on unmanned aerial vehicle (UAV) with compact, small, and simple configuration. The design of circular polarization (CP) is realized by truncating the whole three tips and adjusting the parameters of antenna at the target frequency, f = 5.2 GHz. The results of characteristic performance and S-parameter for the LHCP array four patches stack antenna at the target frequency show successively about 9.74 dBic of gain, 2.89 dB of axial ratio (Ar), and -10.91 dB of S-parameter. Moreover, the impedance bandwidth and the 3 dB-Ar bandwidth of this antenna are around 410 MHz (7.89%) and 100 MHz (1.92%), respectively.